Antifungal mechanisms of activated murine bronchoalveolar or peritoneal macrophages for Histoplasma capsulatum. - Brummer, E (1995)
The first line of defence against natural infection by Histoplasma capsulatum (Hc) consists of bronchoalveolar macrophages (BAM) and an early inflammatory response in the lungs. Little is known about the interaction of BAM and Hc, consequently we studied murine BAM in vitro to assess their role in the pulmonary defence in histoplasmosis. A short-term 3-h assay was used to measure fungicidal activity of control BAM and interferon-gamma (IFN-gamma) plus lipopolysaccharide (LPS)-activated BAM. Fungistatic activity of BAM was determined with a 24-h assay. A method devised for measuring colony-forming units (CFU) of non-ingested non-adherent and adherent ingested yeast cells of Hc in BAM cocultures was used. Activated BAM killed Hc (reduced inoculum CFU by 25 +/- 12%; n = 4). The fungicidal activity of BAM was abrogated by 0.2 mM NG-monomethyl-L-arginine (NMMA) or catalase but not by superoxide dismutase. In fungistatic assays activated BAM inhibited multiplication of Hc by 61 +/- 4% (n = 3) compared with cocultures with control BAM. However, Hc multiplied 100% more in control BAM cocultures than in medium alone. Data indicated that this was due to advantages that Hc has in the intracellular environment. Only NMMA inhibited fungistatic activity of activated BAM. In experiments with peritoneal macrophages (PM), results similar to those with BAM were obtained. In conclusion, activated BAM and PM kill yeast cells of Hc by a mechanism dependent on hydrogen peroxide and products of the nitric oxide synthase (NOS) pathway, whereas fungistasis depends only on products of the NOS pathway.